You are on page 1of 8

ELECTRIC MACHINE DYNAMIC BEHAVIOUR

HOMEWORK REPORT

Reference-frame Theory

By:
Aryo Putro Sadono
23214070
Date:
Monday/February 23, 2015
Lecturer:
Prof. Dr. Ir. Yanuarsyah Haroen

Electric Energy Convertion Research


Laboratory
School of Electrical Engineering and
Informatics
Bandung Institute of Technology
2015

9. The inductance matrix which describe the self- &


mutual inductance between the stator windings of a
salient-pole synchronous machine is given below.

Ls =

Lls +L A LB cos 2 r
1

L A LB cos 2 r
2
3
1

L A LB cos 2 r +
2
3

(
(

(
(

L A LB cos 2 r +
2
3
1
L LB cos 2 ( r + )
2 A
2
Lls +L A LB cos 2 r +
3

Evaluate

K rs Ls ( K rs)

assumed

r =0 , so that

)
)

L A LB cos 2 r
2
3
2
Lls + L AL B cos 2 r
3
1
L LB cos 2 ( r + )
2 A

Lls + L A LB cos 0

Ls= 1 L A LB cos 2
2
3
1
2
L A LB cos
2
3

( )

1
2
L LB cos
2 A
3
4
Lls + L A LB cos
3
1
L L B cos ( 2 )
2 A

( )
( )

][

1
2
L LB cos
Lls + L A LB cos 0
2 A
3
1
1
2
L LB cos ( 2 ) =
L LB cos
2 A
2 A
3
4
1
2
Lls + L A LB cos
L A LB cos
3
2
3

( )

( )

( )
( )

1
L
2

Lls + L

1
2

with:

K rs =

2
sin r
3
1
2

r =0 ,

K rs =

Ks

[
[

1
2

1
2

( 23 ) cos ( 23 ) cos 0
2
2
2
sin (
sin
=
( 3 ) 3 sin 0
3 )

cos 0 cos

2
sin 0
3
1
2

and

]
][

( 23 ) cos ( + 23 )
2
2
sin (
sin ( +
)
3
3 )

cos r cos r

1
2

( K rs )

1
2

1
2

][

( 23 ) cos( 23 ) cos 0
2
2
2
sin ( ) sin (
=
sin 0
3
3 ) 3
cos

1
2

1
2

( 3 ) cos

sin ( ) sin (
3
cos

1
2

is an orthonormal matrix and circular symmetrical, so that the

module of the row or column = 1.

1
2

And it can be shown that for the inverse transformation


1

( K rs )

=( K rs ) orthogonal nature

( [ ]) [ ]
1
2
3
2
1
2

1
2
3
2
1
2

by taking the equation

Ls

( K rs )

2
0
3
1
2

1
2
1
2
1
2

2 1 3
2
3 2
1 3
2
2

namely:

Ls=K rs L s ( K rs )

Then it can be shown that:

[ ][
[ ][
[ ][
1

Ls =

2
0
3
1
2

2
0
3
1
2

2
0
3
1
2

1
2
3
2
1
2

][ ]

1
1
1
1
1
1
Lls + L A LB
L A + LB
LA+ LB
2
2
2
2
2
3 1 L + 1 L L + L + 1 L 1 L L 2 1
ls
A
B
2
3 2
2 A 2 B
2 B
2 A
1 1
1
1
1
1
LA+ LB
L A LB Lls + L A + LB
2
2
2
2 2
2

1
Lls + L A LB
2
3 1 L + 1 L
2
2 A 2 B
1 1
1
L A + LB
2
2
2

1
2
3
2
1
2

3
3
1
Lls + L A LB
0
2
2
2
3 1 L 3 L + 3 L 3 L + 3 L + 3 L
ls
2 ls 4 A 4 B
2
2 A 2 B
2
1 1
3
3
3 L + 3 L + 3 L
Lls L A + LB
2

2
4
4
2 ls 2 A 2 B

1
1
1
L A + LB
2
2
1
1
L A LB
2
2
1
1
Lls + L A + L B
2
2

3
2
3
2

][ ]

1
2
3
2
1
2

1
1
L A + LB
2
2
1
Lls + L A + LB
2
1
L L B
2 A

1
L
2 ls
1
Lls
2
1
Lls
2

3
2
3
2

1
2
1
2
1
2

1
2
1
2
1
2

2
3

3
3
3
Lls + L A LB
2
2
2

3
3
3
Lls + L A + L B
2
2
2

0
3
L
2 ls

][

3
3
Lls + L A L B
2
2

0
3
3
Lls + L A + LB
2
2
0

0
0

0
0
Lls

The magnetizing inductances are defined as

3
Lmq= ( L A LB )
2
3
Lmd= ( L A + LB )
2
obtained:

r
s

K Ls ( K

r 1
s

Lls + Lmq
0
0
=
0
Lls + Lmd 0
0
0
Lls

in which:

3
3
Lls + Lmq =Lls + L A LB =quadrature axisinductance
2
2
3
3
Lls + Lmd =Lls + L A + LB=direct axis inductance
2
2
Lls=zero sequenceinductance

18.
It is often suggested that K s should be changed
so that ( K s ) T =( K s )1 . For example, if

Ks=

Then

2
sin
3
1
2

][

( 23 ) cos( + 23 ) 23 cos
2
2
sin ( ) sin (+
= 2 sin
3
3 )
3

cos cos

T
1
( K s ) =( K s )

1
2

1
2

1
3

( )
2
2
sin ( )
3 3
2
2
cos
3
3

1
3

2
2
cos +
3
3

( )
2
2
sin (+
3
3 )
1
3

. Show that this is true. Also, show that in this case

f 2as + f 2bs +f 2cs=f 2qs +f 2ds+ f 20 s


The cofactor matrix

Ks

replacing each element of

associated with a square matrix

Ks

with its cofactor. If

Ks

is obtained by

det K s 0 , then

][
=

3
Lls + ( LA
2
0
0

c T

1
( Ks) =

adj K s ( K s )
1
=
=
det K s |K s| |K s|

K s11 K s12 K s13


K s21 K s22 K s23
K s31 K s32 K s33

We calculate all cofactors for this matrix.

1 +1

K s11 =(1 )

K s21=(1 )2+1

K s31=(1 )3+1

K s12=(1 )1+2

K s22=(1 )

2+2

K s32=(1 )3+2

K s13=(1 )

1+3

|
)
|
)
)|

2
2
sin
3
3
1
3

2
2
cos
3
3
1
3

2
2
cos +
3
3
= (1 )3
1
3

( )
2
2
sin ( )
3
3

2
2
cos +
3
3

2
2
cos
3
3

2
2
sin +
3
3
2
=(1 )
1
3

(
2
2
sin ( +
3
3

|
|
|
|

= (1 )4

2
sin
3
1
3

2
cos
3
1
3

2
2
cos +
3
3
4
=(1 )
1
3

2
cos
3

2
2
cos +
3
3

2
sin
3
2
sin
3
1
3

2
2
sin +
3
3
=(1 )3
1
3

2
2
sin
3
3

)( 13 ) 23 sin (+ 23 )( 13 )}= (1) 32

2
2
cos
3
3

)( 13 ) 32 cos (+ 23 )( 13 )}=(1

2
2
cos
3
3

)( 23 sin (+ 23 )) 23 cos (+ 23 )

{ ( )

2
1
2
2
sin
sin +
3
3
3
3

)( 13 )}=(1) 32 {sin sin (

2
1
2
2
cos
cos +
3
3
3
3

( )

)( 13 )}=( 1) 32 {cos cos (

( ) =(1) 2 cos 2 sin + 2 2 cos + 2 2 sin =(


(
(
)
(
{
}
3
3
3 )) 3
3 )( 3

2
2
sin ( + )
3
3
5

2
2
sin
3
3
4
=(1 )
1
3

{ ( )

2
1
2
2
sin
sin
3
3
3
3

)( 13 )}=( 1) 32 {sinsin (

K s23=(1 )2+3

K s33=(1 )3+3

|
|

2
cos
3
1
3

2
2
cos
3
3
=(1 )5
1
3

2
cos
3

2
2
cos
3
3

2
sin
3

2
1
2
2
cos
cos
3
3
3
3

( )

)( 13 )}=(1) 32 {cos co

( ) =(1) 2 cos 2 sin 2 2 cos 2 2 sin =( 1


{ 3 ( 3 ( 3 )) 3 ( 3 )( 3 )}
2
2
sin ( )
3
3
6

And expanding along the third row, we have

det K s=k s31 K s31 +k s32 K s32 +k s33 K s33=

1 1
1 1 1 1 1
3
+
+
= (111 )= =1
3
3 3 3 3 3 3 3

( ) ( ) ( )

Thus

( )
2
2
sin ( )
3 3

2
2
2
cos cos
3
3
3

K sc = 2 sin
3
1
3

1
3

2
2
cos +
3
3

1
3

1
3

and

2
2
2
cos cos
3
3
3
1
1
2
2
2
( Ks) =
sin sin
(1 )
3
3
3
1
1
3
3

2
cos
3
2
2
cos
3
3

( )
2
2
cos (+ )
3
3

(
(

2
sin
3
2
2
sin
3
3

( )
2
2
sin (+
3
3 )

][
][

2
2
cos cos ( ) cos (+ )
(
)
3
3

2
2
2
2
2
sin (+ ) = 3 sin sin ( ) sin ( + )
3
3
3 3

2
2
cos +
3
3
2
2
sin +
3
3
1
3

)
)

][

(
(

1
cos
3
1
2 cos 2
=
3
3
3
2
1
cos +
3
3

(
(

)
)

1
3

1
3

2
cos
3
2
2
= cos
3
3

( )
2
2
cos ( + )
3
3

sin

) sin ( 23 )
) sin (+ 23 )

1
2
1
2
1
2

2
sin
3
2
2
sin
3
3

( )
2
2
sin ( + )
3
3

T
( Ks) =

2
cos
3
2
2
cos
3
3

2
sin
3
2
2
sin
3
3

( )
2
2
cos (+
3 3 )

( )
2
2
sin (+
3 3 )

][

1
cos
3
1
2 cos 2
=
3
3
3
2
1
cos +
3
3

(
(

sin

) sin ( 23 )
) sin (+ 23 )

1
2
1
2
1
2

For the purpose of becoming familiar with this transformation let

f as =cos t
f 2as =cos2 t

1
f bs= t f cs =sin t
2
1 2
2
f bs= t
f 2cs=sin 2 t
4

Let us first determine expressions for

f qs ,

f ds , and

f 0 s . From

f qd 0 s=K s f abcs
f qs =

[
[

( )
( )]
2
1
2
2
cos t sin + t sin (
sin t sin (+ )
)
3
2
3
3 ]
1
1
f = (cos t+ tsin t )
2
3

2
1
2
2
cos t cos + t cos
sin t cos +
3
2
3
3

f ds=

0s

[
[

f 2qs =

2
1
2
2
cos t cos + t cos
sint cos +
3
2
3
3

f 2ds =

2
1
2
2
cos t sin + t sin
sin t sin +
3
2
3
3

f 20 s=

1
1
1
cos t+ tsint cos t + tsin t
3
2
2

Now assume that

[
[

)(

)][ cos t cos + 12 t cos ( 23 )sint cos( + 23 )]

)][ cos t sin + 12 t sin ( 23 )sin t sin ( + 23 )]

)
2
f qs ,

=0 . Let us evaluate

2
f ds , and

f 0s

2
1
2
2
cos 0 cos 0+ ( 0 ) cos 0
sin 0 cos 0+
3
2
3
3

f 2ds =

2
1
2
2
cos 0 sin 0+ ( 0 ) sin 0
sin 0 sin 0+
3
2
3
3

f 20 s=

1
1
1
1
1
cos 0+ ( 0 )sin 0 cos 0+ ( 0 )sin 0 = (1+ 00 )( 1+00 )=
3
2
2
3
3

)(

t=0 s .

)][ cos 0 cos 0+ 12 ( 0 ) cos (0 23 )sin 0 cos( 0+ 23 )]=

f 2qs =

for

)][ cos 0 sin 0+ 12 ( 0) sin ( 0 23 )sin 0 sin (0+ 23 )]= 23

2
1
f 2qs + f 2ds +f 20 s= + 0+ =1
3
3
1 2
2
2
2
2
2
f as + f bs +f cs=cos 0+ ( 0 ) +sin 0=1+0+ 0=1
4